Reviewed Study on Corporate Governance and Its Aspects: Exploring the Impact of Corporate Governance on Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The primary difference between corporate governance enforcement problems in India and most western economies is that the entire corporate governance approach hinges on disciplining the management and making them more accountable, that means the ‘agency gap’ in western economies represents the gap between the interests of management and dispersed shareholders and corporate governance norms are aimed at reducing this gap. However, in India the problem is the stranglehold of the dominant or principal shareholders who monopolize the majority of the company’s resources to serve their own needs. That is, the ‘agency gap’ is actually between majority shareholders and other stakeholders. Corporate governance issues have received substantial amount of attention because of their clear importance for the economic growth of companies and society at large especially after plethora of corporate scams and fiascos in the recent times. The U.S., Canada, the U.K., European Countries, the East Asian countries, and even India for that matter have witnessed severe strain on their economies together with the failure of several leading companies in the last two decades or so. This has resulted in greater emphasis and attention on the corporate governance issues. The aim of this paper is to analyze the concept of Corporate Governance and Previous studies that were done regarding the Concept.